The palaeontology of Haasgat a preliminary account - Keyser, Andre W (Bernard Price Institute for Palaeontological Research, 1991)
Haasgat is a cave on the steep western slope of the upper reach of the Witwatersrand Spruit, on the farm Leeuwenkloof 480 lQ, in the Brits District. It was heavily mined for flowstone (calcite). The cave contains a deposit offossiliferous cave silt and breccia that was partially removed by the miners and dumped on the steep slopes of the valley. The original entrance was probably a shallow inclined pit, leading into an upper chamber and then into the preserved depository. Both porcupines and carnivores served as accumulating agents for the bones. Fossils of the primates Parapapio and Cercopifhecoides, hyaena (Chasmaporthetes), fox, porcupines, several species of bovids and two species of Hyrax have been recovered. An insufficient number of fossils have been prepared to determine the age of the deposit with certainty. The deposit was provisionally thought to be of Pliocene age because of the occurrence of Parapapio. At this stage it would be unwise to correlate this occurrence with any other caves in this age range. It is concluded that the cave silts were deposited by flash floods, under a wetter climatic regime than that of the present.
Keywords: cave deposit; taphonomy; climate change; South Africa